1997
DOI: 10.1590/s0037-86821997000100009
|View full text |Cite
|
Sign up to set email alerts
|

Febre maculosa no município de Pedreira, SP, Brasil. Inquérito sorológico

Abstract: Casos de febre maculosa brasileira vêm ocorrendo desde 1985 no município de Pedreira. Com o objetivo de avaliar a prevalência da febre maculosa brasileira nessa área endêmica, foram coletadas amostras únicas de soro de 473 pessoas sadias, moradores e funcionários de uma indústria de louças. As amostras obtidas foram testadas através da reação de imunofluorescência indireta (IFA), para determinação do título de anticorpos para ricketttsia do grupo da febre maculosa brasileira. Vinte e cinco (5,3%) foram conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…As compared with other Brazilian seroprevalence studies the rate found here for R. rickettsii was low. Lemos et al (1994Lemos et al ( , 2001), Del Guercio et al (1997), and Galvão et al (2002) found respectively 7.14, 4.2, 5.3, and 10.1% seroprevalence rates in different serosurveys. Despite this low seroprevalence rate, spotted fever group rickettsioses have been increasing in the studied region with an incidence of over 0.5/100,000 inhabitants-year (Costa 2004) compatible with the ongoing epidemic expansion recently reported from some Brazilian southeast regions (Rozental et al 2002, Galvão et al 2003.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…As compared with other Brazilian seroprevalence studies the rate found here for R. rickettsii was low. Lemos et al (1994Lemos et al ( , 2001), Del Guercio et al (1997), and Galvão et al (2002) found respectively 7.14, 4.2, 5.3, and 10.1% seroprevalence rates in different serosurveys. Despite this low seroprevalence rate, spotted fever group rickettsioses have been increasing in the studied region with an incidence of over 0.5/100,000 inhabitants-year (Costa 2004) compatible with the ongoing epidemic expansion recently reported from some Brazilian southeast regions (Rozental et al 2002, Galvão et al 2003.…”
Section: Discussionmentioning
confidence: 89%
“…Except for the R. rickettsii (Lemos et al 1994, Del Guercio et al 1997, Rozental et al 2002) seroepidemiologic data on rickettsial infections is missing in Brazil although null seroprevalence for R. typhi and E. chaffeensis infections has been reported in one recent study by Galvão et al (2002). This same author however, previously reported in his PhD thesis, the presence of antibodies for R. typhi in 3% of humans from Caratinga, state of Minas Gerais, Brazil (Galvão 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1985, three individuals living in the city of Pedreira, in the region of Campinas, São Paulo, presented with symptoms that were compatible with BSF, which was confirmed by clinical diagnosis 14,15 . Up until that moment, there had been no records of the condition in the region 16 .…”
Section: Introductionmentioning
confidence: 91%